Axiale Spondyloarthritis erkennen - Vielitz, Arne (MSK – Muskuloskelettale Physiotherapie, 2021)
Magrey MN, Danve AS, Ermann J et al. Recognizing Axial Spondyloarthritis: A Guide for Primary Care. Mayo Clin Proc 2020; 95: 2499–2508. doi:10.1016/j.mayocp.2020.02.007